Trend of Arabic Language Use in Indonesian Brands: Onomastic Studies on Arabic Shop Names in Tulungagung - Rasyid, Mufti (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2023)
The trend of naming brands in Indonesia is always changing from time to time. In the last decade, there has been a notable change from western language (English or Latin) to Arabic language such as Wardah, Safi, and Zoya. Not only national class brands, local shop names are also increasingly using Arabic. Nowadays, we often see Arabic products and shops in the market such as Al-Azhar, Yasmin, and El-Faza. This study aims to reveal the phenomenon and meanings behind the use of Arabic in naming local brands in Indonesia, especially in Tulungagung. The research is conducted using onomastic studies. Onomastics is one discipline of socio linguistics that studies the etymology, history, and use of names. Using qualitative descriptive method, this study analyzes the form, reference meaning, and function of the use of Arabic language in shop names in Tulungagung. The researcher uses observation, documentation, and interviews to collect the data. The results of this study reveal that the naming system for shops in Tulungagung is conducted using particular techniques like using single words in Arabic or combination of Arabic and English or Indonesian. Meanwhile the origin of the names could be traced to personal (self and family) names, geographic names, or Islamic terms. The purposes of Arabic naming consist of showing the identity of the owner, matching the type of products and service and the emergence of halal life style.  It is in line with the rise of Islamic spirit which is related with the role of Arabic as a symbol of cultural identity.